2017
DOI: 10.1080/15287394.2017.1367139
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of Dracocephalum moldavica L. (DML) on rat cerebral ischemia reperfusion injury

Abstract: Ischemia reperfusion injury (IRI) is closely associated with oxidative stress and inflammatory responses. Dracocephalum moldavica L. (DML), a Chinese herbal medicine is known to exert protective effects on myocardial ischemia reperfusion injury in rats by inhibiting oxidation damage and inflammatory reactions. However, the effectiveness of DML in cerebral ischemia reperfusion injury (CIRI) as a protective substance and the underlying mechanisms remain to be determined. The aim of this study was thus to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Southeastern Xinjiang is rich in D. moldavica, which is used as a popular herb in traditional Uygur folk medicine and serves as a single medicine prescription in the Uyghur Medicine Ministerial Standard. D. moldavica is mainly used for the treatment of a variety of cardiovascular diseases (Guo et al, 2015;Jia et al, 2017;Tan et al, 2017;Shen et al, 2019). Modern pharmacological studies have illustrated that the active ingredients in D. moldavica displayed the ability to prevent or treat neurodegenerative disorders and inflammatory disorders (García-Díaz et al, 2016;Liu et al, 2018), and suppressed the growth and proliferation of various types of cancer cells (Sato et al, 2015;Chakrabarti and Ray, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Southeastern Xinjiang is rich in D. moldavica, which is used as a popular herb in traditional Uygur folk medicine and serves as a single medicine prescription in the Uyghur Medicine Ministerial Standard. D. moldavica is mainly used for the treatment of a variety of cardiovascular diseases (Guo et al, 2015;Jia et al, 2017;Tan et al, 2017;Shen et al, 2019). Modern pharmacological studies have illustrated that the active ingredients in D. moldavica displayed the ability to prevent or treat neurodegenerative disorders and inflammatory disorders (García-Díaz et al, 2016;Liu et al, 2018), and suppressed the growth and proliferation of various types of cancer cells (Sato et al, 2015;Chakrabarti and Ray, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The myocardial protective function of total flavonoid extract from D. moldavica L. has also been reported [13,20]. Recently, our group further demonstrated that D. moldavica L. attenuated cerebral ischemiareperfusion injury in rats by inhibiting inflammation and oxidative stress [21]. To date, however, the exact molecular The preliminary antioxidant activity results showed that the EtOAc fraction of D. moldavica L. ethanol extract exhibited the remarkable highest antioxidant activity in the four obtained fractions.…”
Section: Discussionmentioning
confidence: 63%
“…MDA is considered the index of lipid peroxidation [21]. In addition, GPx and SOD are antioxidant enzymes, involved in the catalytic detoxification of superoxide and hydrogen peroxide [22, 23]. The conversion content of MDA, and the activity of GPx and SOD in the rat cortex samples proved that oxidative stress occurred following TBI [24, 25].…”
Section: Discussionmentioning
confidence: 99%